Causes and remedial measures of presenteeism in the post Covid-19 era workplace: Insight from job demands-resources theory - Ugochukwu D. Abasilim; Oluwatumininu O. Adebajo; Daniel E. Gberevbie (Faculty of Social and Political Science, Universitas Airlangga, 2022)
The COVID-19 pandemic has put many organizations under pressure to remain active and profitable despite the compulsory long break it gave everyone. There is growing concern that many employees are under pressure to be present at work to fulfil job demands that were not met at the height of the COVID-19 pandemic. This situation has given rise to presenteeism, where workers do not work to their maximum potential. Several theories account for the reasoning behind presenteeism. This paper examines the job demands-resources theory of presenteeism related to the causes and remedial measures that can be put in place in coping with the consequences of presenteeism in any given organisation. Secondary data sources were adopted for this study. The data collected were analysed based on the research questions and presented thematically. The findings reveal that most organizations continue to increase the workload without the required resources necessary to accomplish the job demands. The study recommends that those at the helm of affairs should note the job demands assigned to their employees and make available all the resources to attend to the job demands in order to achieve the overall good of the organization even in the era of the COVID-19 pandemic.